Diagenesis and petrophysics of regional sandstone suites in Southern Apennines Foreland Basin, Italy - Civitelli, Massimo; Borrelli, Mario; Criniti, Sara; Ravidà, Domenico; Falsetta, Ettore (Rendiconti Online Societa Geologica Italiana, 2023)
The southern Apennines foreland region preserves deep-marine turbiditic clastic wedges with contrasting and mixed petrofacies, including 5 distinctive sandstone suites: I) quartzarenite suite of the Numidian Sandstone, II) quartzolithic sandstone suite of the Corleto Perticara Formation, III) quartzofeldspatolithic sandstone suite of the Cilento Group (San Mauro and Albidona Formations), IV) quartzofeldspathic suite of the Gorgoglione Formation, V) arkose sandstone suite of the Oriolo, Nocara, Castelvetere formations. Since the great complexity of these sediments, the main diagenetic events and the key petrophysical properties were investigated to update a database that could be an effective method for petrophysical parameters prediction for similar foreland petroleum systems. The most widespread diagenetic minerals are carbonate, mainly calcite and dolomite, occurring as replacement on detrital grains or as pore-filling cements, and less quartz, phyllosilicate and Fe-oxides and hydroxides cements. These minerals accounted for a widespread process of cementation that, together with compaction greatly influenced the sandstone suites petrophysics, from the lowest porosity median value (3.2 %) of the Numidian Sandstone to the highest value of the Oriolo Fm. (16,75 %). In fact, these formations show porosity and permeability values depending by detrital modes that control the effect of compaction, cementation and dissolution during diagenesis.
CRIS-Team WoS Importer:2023-04-14

External forcing controls on sandstone diagenesis - Caracciolo, Luca; Janßen, Meike; Ravidà, Domenico; Bonnell, L.; Heins, W.; Lander, R.; Stollhofen, Harald (ResTech 2020, 2020)
CRIS-Team Scopus Importer:2020-12-18

Holocene fluvial depositional regimes of the Huab River, Skeleton Coast, Namibia - Walsh, Ella; Caracciolo, Luca; Ravidà, Domenico; Burrough, Sallie; Thomas, David (Earth Surface Processes and Landforms, 2022)
Dryland fluvial systems respond to hydroclimate changes on Quaternary timescales, yet deciphering the palaeoenvironmental histories they preserve is often complex. Whilst hydrological signals are preserved in sediment stores as variations in sediment amount, character, and composition, studies in dryland settings such as Namibia that link sedimentological and compositional changes to palaeoflow are limited. Focusing on the Huab River, Skeleton Coast, this paper presents the first integrated study of textural, compositional, and stratigraphic features from a Namibian fluvial archive. Petrographic and heavy mineral assemblages from Raman laser spectroscopy are combined with lithostratigraphic and particle size analysis. Together with a chronology established through 42 optically stimulated luminescence ages, we reconstruct provenance, changes in river style, and fluvial response to climate. The Huab lithostratigraphic record details periods of flashy ephemeral flow interbedded with flow within well-defined channels. Compositional assemblages indicate that humid conditions during the early to mid-Holocene resulted in activation of sediment stores across the catchment. Episodic discharge within an ephemeral river from 12 to 9 ka was followed by a more sustained river flow in a channelized system from 7 to 5 ka. During the late Holocene, better hydraulic sorting, increased mechanical breakdown of polycrystalline grains, and flash flood lithofacies suggest that flow occurred within a more arid climate. This fine-scaled analysis of an ephemeral fluvial system indicates the utility of assessing compositional changes to distinguish between depositional regimes. This is an important approach for reconstructing fluvial response to climate and for obtaining palaeoenvironmental records from complex sedimentary archives in dryland river settings.
CRIS-Team Scopus Importer:2022-03-18
Keywords: facies analysis; heavy minerals; Holocene; Namibia; OSL dating; palaeoflow; petrography; Raman spectroscopy; sedimentary environment

Reconstructing environmental signals across the Permian-Triassic boundary in the SE Germanic Basin: A Quantitative Provenance Analysis (QPA) approach - Caracciolo, Luca; Ravidà, Domenico; Chew, David; Janßen, Meike; Luensdorf, Keno Nils; Heins, William A.; Stephan, Tobias; Stollhofen, Harald (Global and Planetary Change, 2021)
Global tectonic and climatic models for the Permian-Triassic boundary (PTB) are highly debated. One of the most disputed topics is the temperature increase associated with CO2 emissions generated by the Siberian Trap volcanism and its potential influence on chemical weathering and associated variations in sediment fluxes. By integrating crustal architecture, plate modelling, structural kinematics, and two climatic models, we reconstruct the drainage evolution of Variscan tectonostratigraphic units from the SE portion of the Germanic Basin, from which we also extract the parameters necessary to calculate sediment flux across a time-scale of 28 Ma (Guadalupian-Lower Triassic). We reconstruct the sedimentary response to climatic and tectonic perturbations using Quantitative Provenance Analysis (QPA) and integrate compositional data into a sedimentological framework, paleodrainage and paleoclimatic models. Raman heavy mineral analysis, as well as geochronology and geochemistry of detrital apatite, zircon, and rutile, document variation in drainage lithologies and sediment flux which are controlled by regional extensional tectonics and increasingly humid conditions at the PTB. The sedimentary successions of the SE Germanic Basin record climatic perturbations on a 104 years timescale, while the effects of tectonics are visible on a 106 years timescale. The interplay of climate, tectonics and lithology, and their effects on sediment production and drainage evolution resulted in changes in sediment flux from 2.3 Mt./yr during the Guadalupian (Capitanian), to 3.80 Mt./yr in the Lopingian (Changhsingian) to 7.44 Mt./yr at the end of the Lower Triassic (Olenekian). The multifaceted workflow provided in this study represents the first step towards more precise reconstructions of sediment routing systems in deep-time and provides the first ground-truthed quantification of sediment flux across the Permian-Triassic Boundary.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Tectonic and climatic perturbations; Environmental signals; External forcing controls; Quantitative Provenance Analysis; Permian-Triassic Boundary

Reconstructing environmental signals across the Permian-Triassic boundary in the SE Germanic basin: Paleodrainage modelling and quantification of sediment flux - Ravidà, Domenico; Caracciolo, Luca; Heins, William A.; Stollhofen, Harald (Global and Planetary Change, 2021)
Reconstructing sediment load in deep-time is one of the greatest challenges in the reconstruction of ancient sediment routing systems, particularly because solid statistical models are absent and paleo-climatic, paleo-tectonic, and sedimentary constraints are lacking. This study proposes a reliable workflow for the estimation of paleo-sediment fluxes (Qs) applying the BQART model to a case study from the SE Germanic Basin across the Middle Permian – Early Triassic interval. The input parameters of the simulations derive from: integrated plate modelling and structural kinematics; paleodrainage and paleogeographic reconstructions; global circulation models; and sandstone compositional signatures. We apply Monte Carlo simulation to overcome the input uncertainties for eight different scenarios obtained from the combination of two area estimates, two climate models, and two time resolutions. All the models are in general agreement and show changes in sediment flux (i) being steady or declining slightly through the Middle Permian, (ii) an increase of 31% at the beginning of the Late Permian (3.6–4.6 Mt yr−1), (iii) and a nearly 100% rise at the onset of the Early Triassic (7.4 Mt yr−1). The variation of sediment load across the PTB is coeval to the transition from meandering/sabkha to perennial braided depositional settings recorded from the well data of Obernsees-1 and Lindau-1; it results from both increased tectonism and seasonal precipitation. The Qs estimates agree with those of modern drainages under analogous environmental conditions, highlighting the reliability of the workflow included in this study for the quantification of sediment flux in deep time. Furthermore, the results of this study provide new insights on the highly debated evolution of the continental sequences across the PTB with strong implications for both past and future paleo-environmental reconstructions.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Central European Basin Systems; External forcing controls; Paleodrainage reconstruction; Permo-Triassic boundary; Sediment flux; Sediment routing system

Towards an improved discrimination and correlation of Permian-Lower Triassic sediments in Central Europe: A chemostratigraphic approach - Ravidà, Domenico; Caracciolo, Luca; Heins, William A.; Stollhofen, Harald (Sedimentary Geology, 2023)
The stratigraphic classification and correlation of Permian-Lower Triassic clastic beds in the Central European Basin System traditionally rely on geophysical, bio-, and lithostratigraphic methods. However, in basin margin areas, the accuracy of these tools is diminished due to the heterogeneous distribution of stratigraphic markers, lack of index fossils, and greater climatic and tectonic disturbance. To overcome these limitations, this study introduces a more versatile, multifaceted and chemostratigraphy-based approach. By integrating results from bulk X-ray fluorescence analysis, sandstone petrography, Raman heavy mineral analysis, lithofacies characterisation and borehole gamma-ray logs, we produce robust multi-stratigraphic schemes for selected sequences in the Franconian Basin (SE Central European Basin System). Hierarchical chemostratigraphic zones, comprising five chemozones and sixteen subzones, were designed using key elemental ratios (Ga/Rb, Rb/K, Na/K, Ca/Mg, Cr/Ti, Th/Ti, Nb/Th, Ti/Nb, P/Ti, Zr/P, Zr/Y), whose changes through time reflect modifications in the mineralogical composition of sedimentary rocks. To ensure precise interpretations of geochemical data, we established links between mineralogical and chemical components through statistical processing and direct comparison with mineralogical assemblages. Our results demonstrate that chemostratigraphic boundaries can identify major changes in palaeo-depositional environments and sediment sources induced by eustatic, tectonic and climatic disturbances. For example, changes in the P/Ti and Zr/P ratios across the CP3-CT1 document the increased abundance in apatite-rich granitic detritus, resulting from the exposure of new source lithologies in the catchment area due to Early Triassic synsedimentary tectonism. Since these perturbations had a regional impact on sedimentation, their geochemical fingerprints are correlated across the basin, regardless of lithofacies variability or distance between sections. Moreover, integrating characteristic geochemical signals into multi-stratigraphic schemes enables more precise placement of stratigraphic boundaries, identification of locally deposited/preserved stratigraphic markers, and overall refinement of outdated classification schemes. The chemostratigraphic approach introduced in this study offers a solution to the limitations of conventional stratigraphic tools, allowing robust characterisations and correlations of Permian-Triassic sequences in the marginal regions of the Central European Basin System. In addition, the multi-analytical workflow for processing geochemical data, refining stratigraphic schemes and attributing geochemical anomalies to environmental perturbations represents a further step towards more precise applications of chemostratigraphy to the depositional record.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Basin-scale correlation; Central European Basin System; Chemostratigraphy; Clastic sediments; External forcing controls; Permo-Triassic boundary